Tinjauan Yuridis terhadap Dampak Eksploitasi Perdagangan Anak dengan Modus Perkawinan - Anak Agung Ngurah Bagus Arya Bhaskara; I Nyoman Gede Sugiartha; Diah Gayatri Sudibya (Warmadewa Press, 2021)
The main causes of sexual crimes are economic factors and a lack of formal education, which triggers the crime of sexual exploitation of child trafficking with the marriage mode, which usually targets mostly children or women. This study aims to determine the impact of the exploitation of child trafficking by means of marriage as seen from the aspects of the Law on Trafficking in Persons and to find out the sanctions against perpetrators of child trafficking with the mode of marriage that occur in Indonesia. This research uses the normative legal method. The results of the analysis show that the impact that can be had on children and women victims is the impact on physical and psychological, emotional, spiritual, and disturbed health. Then, sanctions against perpetrators are regulated in Article 297 contained in the Criminal Code and in Law Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons, Law Number 23 of 2002 Concerning Child Protection and also Law Number 13 concerning Manpower.